MicroRNA-181a* Targets Nanog in a Subpopulation of CD34+ Cells Isolated From Peripheral Blood - Paul J Mintz; Pål Sætrom; Vikash Reebye; Marie B Lundbæk; Kaiqin Lao; John J Rossi; Karin ML Gaensler; Noriyuki Kasahara; Joanna P Nicholls; Steen Jensen; Abdelali Haoudi; Mohamed M Emara; et al. (Elsevier, 2012)
Exploiting the properties of stem cells by microRNA (miRNA) profiling offers an attractive approach to identify new regulators of stem cell fate. Although numerous miRNA have been screened from hematopoietic stem cells (HSC), the targets corresponding to many of these miRNA have not yet been fully elucidated. By miRNA profiling in a subpopulation of CD34+ cells isolated from peripheral blood, we have identified eight clusters of miRNA that were differentially expressed. Further analysis of one of the clusters by bioinformatics revealed that a miRNA, miR-181a*, which is highly expressed in the adherent CD34+ cells, affects the expression levels of Nanog, a stem cell surrogate marker. We show specifically by reporter assay and mutational analysis that miR-181a* targets a seedless 3' compensatory site in the 3'UTR of Nanog and affects gene expression. We demonstrate that inhibiting miR-181a* upregulates the Nanog expression level, in addition to an increase in alkaline phosphatase activity. Our studies suggest that miR-181a* may be important in controlling the expression level of Nanog in a subpopulation of CD34+ cells.